Investigating the characteristics of expressed preferences for reducing the impacts of air pollution: A contingent valuation experiment - Ian J. Bateman; Stavros Georgiou; Ian H. Langford; Gregory L. Poe; Tsoumas; Andreas (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2002)
This paper presents the findings of research intended to investigate the nature of expressed preferences for reducing air pollution impacts. Specifically a contingent valuation (CV) experiment is designed to elicit individuals' values for reducing these impacts and examine how these may change when multiple schemes for reducing differing impacts are valued. Results indicate substantial substitution effects between a scheme delivering improvements to human health and one to reduce impacts upon plant life such that the value of a combined programme, delivering both types of benefit, is substantially less than the sum of values for the two separate schemes implemented in isolation of each other. A practical consequence of these findings is that estimates of the value of combined programmes may not readily be obtained by summing the values of their constituent parts.
Keywords: 330; Air pollution; anomalies; Contingent valuation; experimental surveys; part-whole effect; Willingness to pay; Empirische Methode; Luftreinhaltung; Offenbarte Präferenzen; Test; Theorie